Implementation of Behavioral Theory in Learning of Competency-Based Nursing Practices - Rasmun Rasmun; Joko Sapto Pramono; Hilda Hilda; Grace Carol Sipasulta (Health Notions, 2018)
Nursing vocational education is an education that emphasizes the competence or performance of certain skills, which is supported by good attitudes and behavior and extensive knowledge of the area of expertise. So that later they can carry out the task of providing health services in accordance with community expectations. To get high skills during clinical learning it is necessary to apply a learning theory model that allows students to achieve these skills and skills. The implementation of the behavioral theory according to the author is a model theory that allows it to achieve the objectives of learning clinical practice based on competence. The emphasis on behavioral theory focuses on changing the mindset and behavior of a person, in this case, students will imitate or model the model. Learners learn by imitating the correct practices and then doing the same actions and doing so many repetitions. Students who are required to carry out a practicum program for 3 weeks with a duration of 18 days by practicing as many as 75 times the same actions, for example taking action in the form of a physical examination with all the right techniques and methods in different patients, can be ascertained students become teachers/proficient in need, and good attitude. Keywords: Nursing student, Behavioral theory in learning, Competency-based nursing practices, Imitation, Repetition